The Words That Keep People Apart. Official Language, Accountability and Fiscal Capacity - Adelaide Baronchelli; Alessandra Foresta; Roberto Ricciuti (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper empirically evaluates the impact of accountability on fiscal capacity. It adopts an instrumental variable approach using, as an instrument, the measurement of how far, on average, official language differs from ordinary language. The main hypothesis is that if the average citizen cannot understand the central government and the elite, she will find it difficult/impossible to hold the government to account. The first stage results suggest that this instrument is strong and reliable and is negatively correlated with our measure of accountability in line with the hypothesis. The results in the second stage support the main hypothesis. Our results are robust to plausible exogeneity tests and different specifications.
Keywords: H20; D02; D72; C26; 330; language; accountability; fiscal capacity; insulation